PELAKSANAAN KEGIATAN MEMBUKA DAN MENUTUP PELAJARAN PADA KELAS X2 DAN XI IPS1 OLEH GURU SEJARAH DI SMA N 3 MUARA BUNGO JAMBI - Febry, Detti Joha; Bustamam, Bustamam; Iryasman, Iryasman (Pendidikan Sejarah, 2013)
This research is motivated by problems most teachers of history have not done opening and closing of the lesson. On the basis of the problem of this research is focused on the implementation of the opening and closing of the lessons in class XI X2 and IPS1 by history teacher in SMA N 3 Muara Bungo Jambi. This study aims to determine how the implementation of the opening and closing of the lessons in SMA N 3 Muara Bungo Jambi. Ideally the implementation of the opening and closing of the lesson should prepare students psychologically and physically, appersepsi or review the materials that have been studied previously, explaining the learning objectives, deliver measures that will be taught the material, making conclusions or summarize the learning materials, reflection, exploring the opinion learners and provide questions in writing or orally. Based on these problems, the type of research used in this study is the evaluation study. To test the validity of the authors using triangulation of data sources. Then the techniques of data analysis in this study using the interactive analysis technique proposed by Huberman Milles, which consists of data collection, data reduction, data display and conclusion. The results showed that high school history teacher in SMA N 3 Muara Bungo shows the implementation of the opening and closing of the lesson by looking at preparing students psychologically and physically yet fully implemented, the implementation appersepsi or review material already learned already performing well, explaining the purpose learning has not been done. deliver measures that will be taught the material has not been done, to make inferences or summarize the learning material has not been fully implemented, the reflection has not been done, explore the opinions of the students already there but not yet fully implemented, provide questions in writing or orally has been implemented. Based on the results of this study concluded that the implementation of the opening and closing of the lessons in class XI IPS1 X2 and history courses in SMA N 3 Muara Bungo has not been run in accordance with the implementation of the opening and closing of the lesson.Â